2018
DOI: 10.1245/s10434-018-6429-2
|View full text |Cite|
|
Sign up to set email alerts
|

Is Low-Volume Disease in the Sentinel Node After Neoadjuvant Chemotherapy an Indication for Axillary Dissection?

Abstract: Low-volume SLN disease after NAC is not an indicator of a low risk of additional positive axillary nodes and remains an indication for ALND, even when not detected on intraoperative FS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 23 publications
1
66
1
8
Order By: Relevance
“…In their report, all false negative (FN) results for touch imprint cytology were due to the small volume of residual disease. This was also seen in the article by Moo et al 9 in which 30% of the 33 false negative results had ITCs on final pathology and 46% had micrometastasis. There is growing recognition that this small-volume disease is relevant in patients after NAC.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…In their report, all false negative (FN) results for touch imprint cytology were due to the small volume of residual disease. This was also seen in the article by Moo et al 9 in which 30% of the 33 false negative results had ITCs on final pathology and 46% had micrometastasis. There is growing recognition that this small-volume disease is relevant in patients after NAC.…”
supporting
confidence: 63%
“…A recent study from Memorial Sloan Kettering evaluating frozen section analysis of SLNs after NAC also found that this approach to intraoperative evaluation was beneficial, finding a false negative rate (FNR) of only 6.2%. 9 These studies support the use of intraoperative analysis in this setting as the decision to proceed with ALND can be made in a single operative setting. This spares patients the anxiety and risks associated with multiple operations, as well as the delays in starting adjuvant radiation.…”
mentioning
confidence: 55%
“…In addition, among the clinically node‐negative, the sentinel node is the only positive node in about 70% of patients (ie, SLNB clears the axilla in most patients). Among clinically node‐positive patients with a positive sentinel node after neo‐adjuvant chemotherapy, 59%‐63% have positive nonsentinel nodes (ie, SLNB does not clear the axilla in most patients). Axillary dissection is currently recommended for clinically node‐positive patients who remain pathologically node‐positive after neo‐adjuvant chemotherapy.…”
Section: Axillary Management For Ypn(+) Patientsmentioning
confidence: 99%
“…For patients who undergo upfront SLNB, the volume of SLN involvement is an important predictor of the presence of non-SLN metastases 2,4,5 but whether this is also the case for patients who undergo SLNB after NAC is not known. This question is clinically important as we continue to work on further de-escalation of axillary surgery for patients who have their involved axillary nodes downstaged by NAC but are found to have small-volume disease in the SLN, either on intraoperative frozen section or on permanent pathologic evaluation.In a recent issue of the Annals of Surgical Oncology, Moo et al 6 report on a large study from Memorial Sloan Kettering Cancer Center that aimed to determine the sensitivity of intraoperative SLN FS after NAC as well as the association between volume of disease in the SLN (by FS or permanent section) and probability of finding additional non-SLN involvement at completion ALND. During a 9-year period (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017), 702 patients (711 cancers) who had SLNB after NAC were evaluated.…”
mentioning
confidence: 99%
“…In a recent issue of the Annals of Surgical Oncology, Moo et al 6 report on a large study from Memorial Sloan Kettering Cancer Center that aimed to determine the sensitivity of intraoperative SLN FS after NAC as well as the association between volume of disease in the SLN (by FS or permanent section) and probability of finding additional non-SLN involvement at completion ALND. During a 9-year period (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017), 702 patients (711 cancers) who had SLNB after NAC were evaluated.…”
mentioning
confidence: 99%